Learning about trauma: cortisol responses, trauma exposure, and emotional reactivity in undergraduate students - Cless, Jessica Danielle (Kansas State University, 2018)
Several courses in higher education may utilize trauma-related content material as a part of the curriculum. In order to reduce the potential for experiencing secondary traumatic stress in college students, it has been recommended that instructors of such courses be purposeful and cautious with the use of trauma-related materials in the classroom (Cunningham, 2004; Kostouros, 2008). Most recommendations for implementation of these materials are based on theory, and there are few empirical studies that examine actual student reactions to trauma-related content. In the current study, both salivary cortisol and mixed-method survey data were obtained from undergraduate students enrolled in an undergraduate trauma course across three semesters. Results indicated that exposure to higher levels of adverse childhood experiences were significantly related to higher cortisol levels after participating in a course lecture with high levels of trauma content. Generally, students reported favorable views and positive experiences in the course overall. Students with higher levels of lifetime exposure to traumatic events had significantly higher levels of emotional reactions to the course. Qualitative results indicated a range of emotional reactions to the course content, with both positive and negative effects. Implications for teaching practice, policy, and future research are discussed.
Keywords: Cortisol; TeachingTrauma